Corn (Zea mays L.) Response of Palm Oil Mill Effluent Plus Zeolite, and Water Availability in Potential Acid Sulphate Soil - Nursanti, Ida; Defitri, Yuza (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Potential use of acid sulfate soils in agriculture is faced by low pH and the presence of a pyrite layer especially in dry conditions. In order for potential acid sulfate soils to support corn growth during the dry season, technological input is needed to improve soil fertility and overcome water availability by organic fertilizer palm oil mill effluent (POME) plus zeolite. The study used a Split Plot Design with two treatment factors. The treatment factors consisted of plots of water availability: C1 = 100%, C2 = 75%, C3 = 50%, C4 = 25%. POME subplot factor: L0 = No POME, L1 = Secondary Anaerobic POME (zeolite 0%) dose of 1000 ml, L2 = POME Acidification Pool (zeolite 10%) dose of 1000 ml. Availability of water and the provision of POME plus zeolite affect pH, organic-C, total-N, P-Bray I, and soil CEC. In terms of plant growth, both treatments also influence canopy dry weight, seed weight, N content, P and proline leaf corn. Palm oil mill effluent acidification pool plus zeolite 10% dose of 1000 ml increases the adaptability of plants to water shortages and the fertility of potential acid sulfate soils, and the growth and production of corn.